2023 Brazilian Society of Rheumatology guidelines for the treatment of systemic sclerosis - Kayser, Cristiane; de Oliveira Delgado, Sandra Maximiano; Zimmermann, Adriana Fontes; Horimoto, Alex Magno Coelho; Del Rio, Ana Paula Toledo; de Souza Müller, Carolina; Camargo, Cintia Zumstein [UNESP]; Lupo, Cristiano Michelini; de Moraes, Daniela Aparecida; Do Rosário E Souza, Eduardo José; Santos, Flávia Patrícia Sena Teixeira; Sekiyama, Juliana Yuri; et al. (Springer Nature, 2024)
Background: Systemic sclerosis (SSc) is a rare chronic autoimmune disease with heterogeneous manifestations. In the last decade, several clinical trials have been conducted to evaluate new treatment options for SSc. The purpose of this work is to update the recommendations of the Brazilian Society of Rheumatology in light of the new evidence available for the pharmacological management of SSc. Methods: A systematic review including randomized clinical trials (RCTs) for predefined questions that were elaborated according to the Patient/Population, Intervention, Comparison, and Outcomes (PICO) strategy was conducted. The rating of the available evidence was performed according to the Grading of Recommendations Assessment, Development and Evaluation (GRADE) methodology. To become a recommendation, at least 75% agreement of the voting panel was needed. Results: Six recommendations were elaborated regarding the pharmacological treatment of Raynaud’s phenomenon, the treatment (healing) and prevention of digital ulcers, skin involvement, interstitial lung disease (ILD) and gastrointestinal involvement in SSc patients based on results available from RCTs. New drugs, such as rituximab, were included as therapeutic options for skin involvement, and rituximab, tocilizumab and nintedanib were included as therapeutic options for ILD. Recommendations for the pharmacological treatment of scleroderma renal crisis and musculoskeletal involvement were elaborated based on the expert opinion of the voting panel, as no placebo-controlled RCTs were found. Conclusion: These guidelines updated and incorporated new treatment options for the management of SSc based on evidence from the literature and expert opinion regarding SSc, providing support for decision-making in clinical practice.
Keywords: Digital ulcer; Disease management; Guidelines; Interstitial lung disease; Raynaud’s phenomenon; Scleroderma; Systemic sclerosis; Treatment